2013
DOI: 10.2298/fuace1302135k
|View full text |Cite
|
Sign up to set email alerts
|

Architectonic analysis of common facilites in European student hostels in 21st century

Abstract: At the global level, the University campuses represent a dominant type of organization of all the living activities of students. This paper dealt with the architectonic analysis of common features of the recent European student hostels, which were constructed as standalone buildings. The analysis presents the advantages and shortcomings of such spatial organization. In detail are considered the common facilities, which are present to a significant degree in such spatial organization, and which can serve as mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The research conducted in an earlier period (Krasić, 2013) indicated that sociologically best designs of student dormitory space organization comprise existence of spaces for common facilities intended for a small group of students. Such type of building was presented on the space organization diagram as a "6 th type".…”
Section: Space Organization Diagrammentioning
confidence: 99%
“…The research conducted in an earlier period (Krasić, 2013) indicated that sociologically best designs of student dormitory space organization comprise existence of spaces for common facilities intended for a small group of students. Such type of building was presented on the space organization diagram as a "6 th type".…”
Section: Space Organization Diagrammentioning
confidence: 99%